Large linear sensitivity of asymmetric structured giant magnetoresistive device with metastable bcc-Cu spacer and auxiliary biquadratic coupling through Rh spacer. (14th April 2021) - Taparia, Dolly; Fathoni, Kresna Bondan; Kulkarni, Prabhanjan Dilip; Srinivasan, Ananthakrishnan; Alagarsamy, Perumal; Sakuraba, Yuya; Nakatani, Tomoya; Sasaki, Taisuke; Hono, Kazuhiro
Abstract: Large magnetoresistance (MR) with a linear response to the magnetic field is an important feature in MR devices for magnetic sensor applications. Following the largest MR ratio realized in a current-in-plane (CIP) giant magnetoresistance (GMR) device using a metastable body-centered cubic (bcc)-Cu spacer, we developed a new CIP-GMR device with a combination of two spacer materials, i.e. CoFe/Rh/CoFe (sensing layer)/bcc-Cu/CoFe asymmetric structure and realized a large linear sensitivity due to large MR ratio (21%) and linear response through a biquadratic coupling, high sensitivity of 0.047% mT −1, reduced nonlinearity of 0.98% full scale along with a substantially wider operation field range of 220 mT. Our numerical simulation analyses of magnetization curves clearly establish that the middle CoFe sensing layer is well-controlled by interlayer exchange coupling through the Rh spacer, giving rise to a linear response without losing the high MR ratio through the bcc-Cu spacer. These findings demonstrate that CIP-GMR devices are promising for wide dynamic range magnetic sensors.